Cloud-based video systems: A review of security threats and solutions - Hatwalne, Prasad A; Dhore, Abhishek; Badgujar, Rinku; Brahme, Manoj; Pardey, Minal A (Review of Computer Engineering Research, 2025)
With the rapid growth of cloud computing, along with the recent development of video-based applications and social platforms, there is a need for cloud-based video frameworks. These frameworks employ scalable and economical methods for processing, storing, and delivering video content. The shift to the cloud for video services introduces many security concerns that can compromise the integrity, confidentiality, and availability of the video data they handle. Data breaches, unauthorized access, distributed denial of service (DDoS) attacks, vulnerabilities in encryption, and access control mechanisms are the main security challenges faced by cloud-based video frameworks, which this paper thoroughly reviews. This paper explores the challenges and discusses how they can affect both service providers and end users. The review also highlights state-of-the-art solutions presented in the literature and best practices to mitigate these threats. Some prominent solutions include encryption techniques, access control models, intrusion detection systems, and privacy-preserving algorithms. Additionally, the document addresses how advanced technologies like AI and blockchain can be used to enhance the security of cloud-based video services. This review compiles recent research and industry practices, providing a comprehensive overview of the current security posture and effective strategies for constructing a more secure cloud-based video framework in the future.